Biocatalysis and Pharmaceuticals: A Smart Tool for Sustainable Development - Alcantara, Andres R (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Biocatalysis, that is, the use of biological catalysts (enzymes, cells, etc.) for the preparation of highly valuable compounds is undergoing a great development, being considered an extremely sustainable approach to undertaking environmental demands. In this scenario, this book illustrates the versatility of applied biocatalysis for the preparation of drugs and other bioactive compounds through the presentation of different research articles and reviews, in which several authors describe the most recent developments in this appealing scientific area. By reading the excellent contributions gathered in this book, it is possible to have an updated idea about new advances and possibilities for a new exciting future.
English
Keywords: n/a; biotransformations; glycosidases; bacteria; OcUGT1; antioxidant activity; glycodiverfication; benzoxathiepins; coprostanol; 7-methylguanosine iodide; sulfuretin; chondroitin sulfates; 7-methylguanine arabinoside iodide; 7-methyl-2?-deoxyguanosine iodide; microalgae; chitosan oligosaccharides; deacetylation degree; cholesterol; Tecadenoson; esterase; metabolic pathways; chitinases; alcohol; transglycosylation reaction; MALDI-TOF; photooxidation; aqueous solubility; ?-transaminase; cascade; nutraceutical; antimuscarinic agents; extraction; rutin oligomers; Alcalase®; HPSEC; Cladribine; purine nucleoside phosphorylase; pleiotropic effects; biotransamination; amino acid; stereoselective; laccase activity; biocatalysis; Ribavirin; lyases; chitosanases; anti-inflammatory; glycosaminoglycan; polysaccharides; amine transaminases; ester hydrolysis; Spirulina; asymmetric synthesis; reductive amination; glycosyltransferase; statins; stereoselective synthesis; xanthine oxidase inhibition; reduction reaction; pig liver esterase (PLE)